Performance Analysis and Simulation of a Diesel-Miller Cycle (DiMC) Engine - Gonca, Guven; Hocaoglu, Mehmet Fatih (SPRINGER HEIDELBERG, 2019)
A comprehensive performance examination of an engine running on combination of the Diesel and Miller cycles called Diesel-Miller cycle in terms of effective power, density of the effective power, and effective thermal efficiency, which will be called engine performance (ENPER) characteristics, is conducted using a novel thermodynamic simulation model. The impacts of cycle design parameters such as cycle pressure ratio, equivalence ratio, effective compression ratio (r), bore/stroke ratio (d/L), average piston speed, friction coefficient, engine speed (N), stroke (L), and air inlet temperature and air inlet pressure on the ENPER characteristics have been investigated. Additionally, the energy losses depending on exhaust output, friction, incomplete combustion, heat transfer have been defined as a ratio of energy provided by fuel injection. Variable specific heat values with respect to temperature variation for working fluid are used to get realistic results. The results of the study are reasonable and unique, and they could be utilized by researchers and engineers studying on internal combustion engines.
Keywords: Engine performance characteristics; Diesel-Miller cycle engine; Performance analysis; Thermal efficiency; Power density; Engine simulation; FINITE-TIME THERMODYNAMICS; VARIABLE SPECIFIC-HEATS; COGENERATION SYSTEM; MAXIMUM POWER; FUEL-ECONOMY; OPTIMIZATION; EMISSION; PARAMETERS; EFFICIENCY; FRICTION; Science & Technology - Other Topics